Anti-allergic activity of natural plant products for the treatment of sensitive skin: A review - Miao-miao Guo; Wan-ting Xue; Lian-ying Liao; Xiao Ling; Dan Yu; Xiao-long Lan; Wei-qiang Zhou; LiLi (Elsevier, 2022)
The environment is being continuously deteriorated by air pollution and global warming, increased pressure of work or family on life, and changes in lifestyle; these factors have contributed to an increase in the proportion of both females and males with sensitive skin. To this end, the cosmetics market has focused on developing hypoallergenic or skin-soothing and make-up products. Here, we summarize the definition and causes of sensitive skin, list the mechanisms underlying the development of this condition, and review the natural plant products and purified active components that have potential for use in anti-allergic cosmetics. A review of studies that evaluated the anti-allergic properties of natural products was conducted. There has been a progressive increase in the number of natural products identified as potential anti-allergic raw materials in cosmetics. Finally, we suggest strategies for developing anti-allergic cosmetics in the future.